Genetics of Osteoporosis - Tural, S.; Kara, N.; Alayli, G. (Galenos Yayincilik, Molla Gurani Cad. 21 Findikzade-Istanul 34093, 2011)
Osteoporosis is a multifactorial disease characterized by a decrease bone mineral density (BMD) and micro-architectural deterioration of bone structure. Although there are several environmental influences on BMD, a genetic contribution to the pathogenesis of osteoroposis has recently been recognized. Twin and family studies have demonstrated an importanat genetic component of osteoporosis regarding many parameters of bone properties with a heredity of 50-80%. The existence of many candidate genes which have effect on bone mass was reported. Association studies based on candidate gene polymorphisms and subsequent meta-analyses, and the more recent genome-wide association studies (GWAS), have clearly identified a handful of genes associated with BMD and other osteoporosis related phenotypes. In this rewiev, after definition osteoporosis, hertitability of osteoporosis was explained by candidate gene approach, linkaj analysis, QTL (Quantitative Trait Loci)'s, family-based and twin studies, animal studies, GWAS meta analysis, gene expression studies and pharmacogenetics. Identifying osteoporosis related genes may provide new routes for therapeutic intervention and osteoporosis prevention. Technological developments, such as genome-wide sequencing and the thousand genome project, will permit identification of these alleles and give a more complete picture of the genetic architecture of osteoporosis. Also further largescale studies and functional analyses can be expected in the future; these will be highly relevant both for he diagnosis of osteoporosis with individual risk profiles, and for nutritional and pharmaceutical treatment.
Osteoporoz Genetiği
Keywords: Bone Mineral Density; Genetics; Osteoporosis